Analysis of Students’ Difficulties in Mathematical Literacy Based on Conceptual Understanding and Mathematical Reasoning (Asimtot : Jurnal Kependidikan Matematika, 2026)
This research aims to identify the types of students’ difficulties in solving mathematical literacy problems based on their conceptual understanding and mathematical reasoning abilities. A descriptive qualitative method was employed. The subjects consisted of 28 students from a public junior high school and 16 from a private junior high school in Langsa City. Data were collected through written tests and interviews. The test instrument consisted of 10 mathematical literacy questions adapted from the Computer-Based National Assessment (CBNA), designed to assess conceptual understanding and reasoning skills. Interviews were conducted with six students selected through purposive sampling, representing high, medium, and low mathematical ability levels from each school. The purpose of the interviews was to explore students’ thinking processes in greater depth. The results showed that the most frequent difficulty encountered by students was applying concepts or algorithms to solve problems, particularly in relation to formulating evidence or reasoning to draw conclusions. Interview findings revealed several underlying causes for these difficulties, including trouble understanding contextual (story-based) problems, confusion about what is known and what is being asked, insufficient conceptual mastery, lack of experience with reasoning-based questions, and difficulty developing effective problem-solving strategies. These findings suggest the need for instructional approaches that strengthen students’ conceptual understanding and reasoning abilities, especially in solving real-world mathematical problems.
Keywords: Difficulty, Mathematical Literacy, Conceptual Understanding, Mathematical Reasoning